THE ROLE OF GENDER IN PARTICIPATORY POLICYMAKING: The Development of Tenun Ikat Industry in Ternate Village Alor Barat Laut District Alor Regency - Djobo, Amon; Liliweri, Aloysius; Djaha, Ajis Salim Adang (International Journal of Social and Management Studies, 2023)
This research aimed to analyze and describe the gender role in participatory policymaking for Small Industries Center Development at Alor Barat Laut District. This research employed a qualitative approach and case study method. The researchers performed the study at Alor Barat Laut District, Alor Regency, Nusa Tenggara Timur, Indonesia. The researchers chose Alor Barat Laut District as the Alor Regency Government (2019 - 2024) established a small industry development strategy in Alor Regency Regional Mid Term Development Plan (Rencana Pembangunan Jangka Menengah Daerah - RPJMD). The research focus was the gender role in participatory policy making. The research sub-focuses are: (1) the role of men and women in past policy-making, (2) the role of men and women in current policy-making, and (3) the role of men and women in future policy-making. The data collection used in-depth interviews, documentation, and observation. The data analysis used Robert Yin's pattern-matching analysis technique visualization. The researchers used the triangulation technique to validate research findings.The research result showed that women were dominant in the past decision-making of the tenun ikat[1] industry. Men were viewed as the inhibiting factor of business development. The women performed the majority of household chores and tenun ikat production. In the past, housewives bartered the tenun ikat products in the traditional market. Therefore, the development and preservation of tenun ikat were entrusted to the women. However, men bartered earthen pottery for cotton from other regions (generally from Flores). In addition, the men (boat masters) carried the tenun ikat products to the traditional markets. The women entrusted the men with procuring material and transporting products as they tended to perform domestic roles.